The Archaeology of Water Management on the Swahili Coast of East Africa - Baumanova, Monika (The Archaeology of Irrigation Technology and Water Management in the Islamic World: Proceedings of the Bahrain Conference, January 2024, 2025)
The archaeology of irrigation technology and water management encompasses a wide range of structures – subterranean tunnels (qanāts, falaj, foggara, ghayl etc.), reservoirs, cisterns, canals, aqueducts, tanks, fountains, water mills, wells, dams, barrages - in a variety of contexts - mountains, deserts, forests, agricultural, horticultural, urban, village, military, riverine, estuarine, coastal, lacustrine – and over a long time period from the seventh through to nineteenth centuries. However, in many areas the archaeology of these facilities remains little explored. This volume begins to rectify this through a variety of case studies examining the diverse ways that past populations have developed hydraulic infrastructure for moving and managing water across the Islamic World. It also considers how past human ingenuity in developing hydraulic infrastructure, now often fallen into disrepair and dis-use, could hold lessons for the present and offer solutions for the future as humanity faces the challenges of environmental and climate change.
Keywords: Archéologie -- Zanzibar

Muslim Burial Customs on the East African coast - Juma, Abdurahman (Tor: meddelanden från Uppsala universitets museum för nordiska fornsaker, 1996)
Keywords: Archéologie -- Zanzibar

The Nineteenth-century Carved Wooden Doors of the East African Coast - Aldrick, Judith (Azania: Archaeological Research in Africa, 1990)
Keywords: Archéologie -- Zanzibar

James Kirkman — an Appreciation - Allen, J. de V. (Paideuma, 1982)
Keywords: Archéologie -- Zanzibar

James Kirkman and East African Archaelogy - Wilson, Thomas H. (Paideuma, 1982)
Keywords: Archéologie -- Zanzibar

Ship graffiti at the Zanzibar Gereza (Old Fort), Stone Town, Unguja, Tanzania - Cooper, John P.; Ghidoni, Alessandro (Azania: Archaeological Research in Africa, 2022)
Keywords: Archéologie -- Zanzibar

Archaeological Approaches to East Africa's Changing Seascapes - Breen, Colin; Lane, Paul J. (World Archaeology, 2003)
Keywords: Archéologie -- Zanzibar

Swahili Cosmopolitanism in Africa and the Indian Ocean World, A.D. 600–1500 - LaViolette, Adria (Archaeologies, 2008)
Coastal peoples who lived along the Eastern African seaboard in the first millennium A.D. onwards began converting to Islam in the mid-eighth century. Clearly rooted in and linked throughout to an indigenous regional Iron Age tradition, they created a marked difference between themselves and their regional neighbors through their active engagement with Islam and the expanding Indian Ocean world system. In this paper I explore three ways in which interrelated cultural norms—an aesthetic featuring imported ceramics, foods, and other items, Islamic practice, and a favoring of urban living—created and maintained this difference over many centuries. These qualities of their identity helped anchor those who became Swahili peoples as participants in the Indian Ocean system. Such characteristics also can be seen to have contributed to Swahili attractiveness as a place for ongoing small-scale settlement of Indian Ocean peoples on the African coast, and eventually, as a target for nineteenth-century Arab colonizers from the Persian Gulf. This paper examines the archaeology of these aspects of Swahili culture from its early centuries through ca. A.D. 1500.
Keywords: Archéologie -- Zanzibar

The spatial dichotomy of Swahili towns: the case of Zanzibar in the nineteenth century - Sheriff, Abdul Mohamed Hussein (Azania: Archaeological Research in Africa, 2002)
Keywords: Archéologie -- Zanzibar

Zanzibar: A Nineteenth-Century Landscape of the Omani Elite - Rhodes, Daniel; Breen, Colin; Forsythe, Wes (International Journal of Historical Archaeology, 2015)
Keywords: Archéologie -- Zanzibar

Islam, Archeology, and Swahili Identity - Horton, Mark (Changing social identity with the spread of Islam: archaeological perspectives, 2005)
Keywords: Archéologie -- Zanzibar

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie -- Zanzibar

At the Origins of the Settlement of Zanzibar: The Cave of Machaga - Wafula, G. K. (Tarehi, 2001)
Keywords: Archéologie -- Zanzibar